The Prospects of Lampung's Pepper Export to the Global Market: An Analysis Using the ARIMA Model - Putri, Najah Hanifah; Abidin, Zainal; Situmorang, Suriaty (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Pepper is one of Lampung's leading export commodities. It can be seen from the contribution of Lampung Province's pepper, which accounted for 42 percent of Indonesia's overall pepper exports. However, pepper production and export volume in Lampung Province continue to decline annually. This study aims to analyze the prospect of Lampung’s pepper export to the international market for ten years, from 2023 - 2033. This research used ARIMA (Auto Regressive Moving Average) t model tool using E-views statistical software to forecast the trend of export of Lampung pepper to the International market. The data used was secondary data from the quarterly export of Lampung’s pepper from 2002 to 2022. The study suggested that Lampung's pepper exports are projected to decrease from 2023 to 2033, with a decrease of 10 percent each year. Finally, in 2033, Lampung's pepper exports to the international market only reached 998 tons.